2016
DOI: 10.1016/j.atherosclerosis.2016.08.043
|View full text |Cite
|
Sign up to set email alerts
|

A phase III randomized trial evaluating alirocumab 300 mg every 4 weeks as monotherapy or add-on to statin: ODYSSEY CHOICE I

Abstract: Alirocumab 300 mg Q4W is a viable additional treatment option in patients requiring LDL-C-lowering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
70
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(81 citation statements)
references
References 19 publications
(17 reference statements)
8
70
0
1
Order By: Relevance
“…5,1014,16,17,25 We observed that evolucumab had lower risk of stroke when compared with no PCSK9 inhibitors (RR 0.75, 95% CI 0.62–0.91), and we did not observe any difference in the risk of ischaemic stroke between the alirocumab and no PCSK9 inhibitors (RR 1.71, 95% CI 0.64–5.36) (Figure 3B). No difference was observed in the risk of neurocognitive deficits between evolocumab (RR 1.42, 95% CI 0.74–2.73) and alirocumab (RR 1.04, 95% CI 0.56–1.94) compared with no PCKS9 inhibitors (Figure 4B).…”
Section: Resultsmentioning
confidence: 65%
“…5,1014,16,17,25 We observed that evolucumab had lower risk of stroke when compared with no PCSK9 inhibitors (RR 0.75, 95% CI 0.62–0.91), and we did not observe any difference in the risk of ischaemic stroke between the alirocumab and no PCSK9 inhibitors (RR 1.71, 95% CI 0.64–5.36) (Figure 3B). No difference was observed in the risk of neurocognitive deficits between evolocumab (RR 1.42, 95% CI 0.74–2.73) and alirocumab (RR 1.04, 95% CI 0.56–1.94) compared with no PCKS9 inhibitors (Figure 4B).…”
Section: Resultsmentioning
confidence: 65%
“…A total of 138 study arms from 35 studies were analyzed, comprising 45 539 patients (Table S1). 5, 11, 12, 13, 14, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43 Alirocumab was used in 18 studies (28 treatment arms), and evolocumab was used in 17 studies (39 treatment arms; Figure 1); placebo was the most common control used (52 control arms), with ezetimibe used in 17 arms, and standard therapy in 2 arms. Eight studies were of an exclusively FH population, and 5 studies included only patients intolerant to statins.…”
Section: Resultsmentioning
confidence: 99%
“…Phase 2 studies indicated that efficacy was not fully maintained over the dosing interval when alirocumab 150 mg Q4W was co-administered with a statin2122, probably because of statin-induced increases in PCSK9 levels leading to increased alirocumab clearance19. However, efficacy was stable with the 150 mg Q2W dose when co-administered with a statin2122, and has also been shown to be relatively stable with a dose of 300 mg Q4W23.…”
Section: Discussionmentioning
confidence: 99%